2017
DOI: 10.1093/gerona/glw248
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Health Span in Caenorhabditis elegans: Lessons From Short-Lived Mutants

Abstract: Genetic changes resulting in increased life span are often positively associated with enhanced stress resistance and somatic maintenance. A recent study found that certain long-lived Caenorhabditis elegans mutants spent a decreased proportion of total life in a healthy state compared with controls, raising concerns about how the relationship between health and longevity is assessed. We evaluated seven markers of health and two health-span models for their suitability in assessing age-associated health in inver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 44 publications
(60 reference statements)
4
44
0
Order By: Relevance
“…Similar to previous studies, across all genotypes there appears to be a consistent initial period of frequent 'high activity' movement, followed by a period of sporadic 'low activity' movement until the individual's death [12][13][14]16]. Bouts of consistent movement suggest an initial period of good health for the worm, which may indicate a lack of sarcopenia or cognitive decline.…”
Section: Health Recapitulates Known Behavior and Longevity Trends In supporting
confidence: 82%
See 1 more Smart Citation
“…Similar to previous studies, across all genotypes there appears to be a consistent initial period of frequent 'high activity' movement, followed by a period of sporadic 'low activity' movement until the individual's death [12][13][14]16]. Bouts of consistent movement suggest an initial period of good health for the worm, which may indicate a lack of sarcopenia or cognitive decline.…”
Section: Health Recapitulates Known Behavior and Longevity Trends In supporting
confidence: 82%
“…Existing methods of studying lifespan and the period of healthy living, or 'healthspan', in C. elegans are limited and lack the ability to provide precise environmental control. Although traditional lifespan and healthspan assays have uncovered important insights into the aging process, they require large amounts of manual labor, making it difficult to scale for different genotypes or environmental conditions [11][12][13][14]. Recent high-throughput methods have been developed for scoring longevity or observing behavior over time [15][16][17][18]; however, they also lack precise control in regulating the organism's immediate environment.…”
Section: Introductionmentioning
confidence: 99%
“…2C). Thus, while nsun-1 knockdown does not extend lifespan, it improves the healthspan parameters thermotolerance and locomotion (Bansal et al, 2015; Rollins et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies in humans have investigated the period at the tail end of life and how it correlates with mortality, and results have demonstrated that although disability generally increases as individuals approach death (38), the rate and severity of decline varies by case and individual (39). Studies in worms (4043) and mice (36, 44) in select genetic backgrounds demonstrate that lifespan extension is not necessarily accompanied by an increase in healthspan. Thus these studies pose the question whether lifespan and healthspan are indeed determined by the same genetic mechanisms.…”
Section: Introductionmentioning
confidence: 99%